Neutrophil gelatinase-associated lipocalin (NGAL/Lcn2) is upregulated in gastric mucosa infected with Helicobacter pylori - Alpízar Alpízar, Warner (2009)
Helicobacter pylori infection is one of the most significant risk factors for gastric cancer. The infection is established early in life and persists lifelong leading to a sustained chronic inflammation. Iron is essential for most living organisms. Bacteria use several mechanisms to acquire iron from their hosts, including the synthesis of the potent iron chelators known as siderophores. Hosts cells may express the siderophore-binding protein neutrophil gelatinase-associated lipocalin (NGAL/lipocalin-2 (Lcn2)) in response to infection, thus preventing bacterial iron uptake. We have characterized here the pattern of expression of NGAL/Lcn2 in gastric mucosa (45 non-neoplastic and 38 neoplastic tissue samples) and explored the connection between NGAL/Lcn2 expression and H. pylori infection. Immunohistochemical analysis showed high NGAL/Lcn2 expression in normal and gastritis-affected mucosa compared to low expression in intestinal metaplasia, dysplasia, and gastric cancer. In normal and gastritis-affected mucosa (n = 36 tissue samples), NGAL/Lcn2 was more frequently seen in epithelial cells located at the neck and base of the glands in H. pylori-positive cases than in similar epithelial cells of noninfected cases (Fisher’s exact test, p = 0.04). In conclusion, the high expression of NGAL/Lcn2 in normal and gastritis-affected mucosa infected with H. pylori suggests that NGAL/Lcn2 is upregulated locally in response to this bacterial infection. It is discussed whether this may have a causal relation to the development of gastric cancer.